Sensitivitas Skema Mikrofisik Awan pada Model WRF untuk Simulasi Hujan Deras di Purworejo Jawa Tengah 20 Desember 2013: Fitria Puspita Sari - Fitria Puspita Sari, Fitria Puspita Sari (Jurnal Fisika dan Aplikasinya, 2025)
On 20th December 2013 03.00 LT (19th December 2013 20.00 UTC) there was a flood at Purworejo regency. The flood caused by heavy rain and strong winds gave bad impact like property’s disadvantage and human victims. Place of the accident is rather far from meteorology office BMKG, being hard for getting the observation’s date. So, it needs WRF model to simulate. In this simulation the difference microphysics scheme to know the sensitivity of this scheme at WRF’s configuration setting has been used. The whole simulation result is successful to identify the presistence of convective cloud that produce rain. The using of microphysics scheme influences the model’s result. Morrison-2 is judged being a best scheme when it is used on the simulation of Purworejo’s flood. But, the model cannot represent intensity of rain and its time exactly, becauseWRF produces rain that intensity is low (underestimate) and it needs more time. Finally we know that the model is only able to simulate the development of convectif cloud, not to produce rain.